2015
DOI: 10.1038/onc.2015.176
|View full text |Cite
|
Sign up to set email alerts
|

A microRNA code for prostate cancer metastasis

Abstract: Although the development of bone metastasis is a major detrimental event in prostate cancer, the molecular mechanisms responsible for bone homing and destruction remain largely unknown. Here we show that loss of miR-15 and miR-16 in cooperation with increased miR-21 expression promote prostate cancer spreading and bone lesions. This combination of microRNA endows bone-metastatic potential to prostate cancer cells. Concomitant loss of miR-15/miR-16 and gain of miR-21 aberrantly activate TGF-β and Hedgehog signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
76
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(79 citation statements)
references
References 66 publications
2
76
0
1
Order By: Relevance
“…No other studies to our knowledge have investigated the effects of miR-15a/16 on TGF-beta3 in pathological mechanisms of diabetic retinopathy. Previous studies, instead, have shown roles of miR-15 and -16 on TGF-beta signaling in other types of disorders, as miR-15/16 upregulated TGF-beta signaling, leading to progression of prostate cancer (Bonci et al, 2016). miR-16 overexpression suppressed TGF-beta release in human alveolar epithelial cells (Tamarapu Parthasarathy et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…No other studies to our knowledge have investigated the effects of miR-15a/16 on TGF-beta3 in pathological mechanisms of diabetic retinopathy. Previous studies, instead, have shown roles of miR-15 and -16 on TGF-beta signaling in other types of disorders, as miR-15/16 upregulated TGF-beta signaling, leading to progression of prostate cancer (Bonci et al, 2016). miR-16 overexpression suppressed TGF-beta release in human alveolar epithelial cells (Tamarapu Parthasarathy et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) have demonstrable potential as diagnostic, predictive, and prognostic markers, and may provide a promising new class of therapeutic targets [1517]. MiRNAs are small 17–25 nucleotide non-coding RNA molecules, which regulate post-transcriptional gene expression in a sequence-specific manner and have a central role in multiple biological functions, including cell survival, proliferation, and DNA damage responses [1820].…”
Section: Introductionmentioning
confidence: 99%
“…PC is challenging to treat due to its high metastasis rate (2); despite considerable advances in the treatment of PC, metastatic prostate cancer (MPC) remains incurable (3). The molecular mechanisms underlying the metastasis of PC cells remain largely unknown and require further study.…”
Section: Introductionmentioning
confidence: 99%